The Impact of a Vegetarian Diet on the Cardiovascular System - Grądalski, Łukasz; Niemirka, Szymon; Dębicki, Filip; Janiak, Aleksandra; Kopaczyńska, Adrianna; Szafrańska, Katarzyna; Dominiczak, Kinga (Quality in Sport, 2025)
The vegetarian diet is gaining increasing popularity worldwide, particularly in developed countries. This phenomenon is driven by various factors, such as concern for animal welfare, growing social awareness about health, and the role of nutrition in maintaining it. Cardiovascular diseases have been the leading cause of death globally for many years, with many risk factors - including diet - being potentially modifiable causes. A vegetarian diet can support the treatment and prevention of cardiovascular diseases. According to the latest available knowledge, it has a particularly beneficial effect on lowering blood pressure, reducing the risk of developing coronary artery disease, and preventing metabolic syndrome. However, exclusively following this diet requires the inclusion of nutritional supplements to address potential deficiencies, preventing the development of other health issues.